Channel bed degradation caused by construction - Nati Yanapirut; Wang, Tsan-Wen; Tawatchai Tingsanchali; Prida Thimakorn (Bangkok : Asian Institute of Technology, 1985)
The study is focused on what factors determine the channel bed degradation caused by constrictions. This investigation is conducted under the static equilibrium theory. Experimental investigation is conducted in a recirculating rectangular flume. the flume is 20 m length, 0.6 m width and 0.8 m depth. Three kinds of sand with median particle diameter 0.5, 0.75 and 1.5 mm are used in this experiment, and 96 runs are performed. The effect of size of sand, Froude number, opening ration, spacing between constriction on the equilibrium depth of scour are studied by verifying the dimensional analysis with the help of experimental data. It is found that the relative depth is not much affected by the size of bed material and Froude number. It is concluded that the relative depth for the scour caused by channel constriction is mainly a function of the constriction ratio and the ratio of spacing and length of the spur dike. An empirical equation is obtained to compute the relative depth.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Sediment transport